PENGARUH DISIPLIN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV DI SD NEGERI 066050 MEDAN DENAI - Rosa Maria S; Reflina Sinaga; Darinda Sofia Tanjung (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article focuses on a study that was designed to determine the level of students’ learning discipline. The type of study was quantitative research. The subjects of the study involved the fourth-grade students of SD Negeri 066050 Medan Denai. Based on the results, there was an effect of discipline on learning outcomes at the fourth-grade level of SDN 066050 Medan Denai in the academic year of 2020/2021. The research instrument was used to measure learning discipline. The instrument was a questionnaire that consisted of 40 items. Meanwhile, to measure students’ learning outcomes, the researcher used math scores. After measuring the learning discipline, the mean (average) score of the questionnaire was 120.3. It means that the learning discipline for students at SDN 066050 Medan Denai was categorized as high level. To determine the effect level between learning disciplines and learning outcomes, the Pearson correlation formula was used. Based on the count result, rcount was 0.609, which meant that the correlation value was strong or correlated. The significance test was carried out to test the hypothesis by comparing the value of tcount with ttable. The value of tcount was 4.062 while ttable was 2.042. Because tcount 4.062 was higher than ttable 2,042, thus Ha was accepted and Ho was rejected. Through the ttest,, it could be concluded that there was a significant relationship between students’ learning discipline and learning outcomes.